"Can The Toyota Production System Improve Productivity?" A Case Study Of An Office Furniture Plant In Malaysia - Tee, Joe Tsung Yen (2004)
The Toyota production System has been proven to be a profit driven in many automotive companies in the world. An office furniture manufacturing plant in asia has intended to assimilate this system into its old practice of managing the company and hopes to implement effective manufacturing practice like any profitable automotive company.